1999
DOI: 10.1046/j.1537-2995.1999.39060639.x
|View full text |Cite
|
Sign up to set email alerts
|

Human T‐lymphotropic virus type I among blood donors from Guadeloupe: donation, demographic, and biologic characteristics

Abstract: New donor status, advancing age, female sex, and positivity for hepatitis B virus core antibodies were the major factors associated with HTLV-I infection in Guadeloupe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…25,26 Taken together, a birth cohort effect should be taken into account in the age-dependent rise in HTLV-I prevalence. 27 This effect observed in this study for HTLV-I suggests that improved screening strategies might be applied to 35 and above years old in Mashhad. On the other hand, a population-based study in French Guiana reported an HTLV-I infection in subjects with all age groups suggesting that other factors might be involved in virus transmission.…”
Section: Discussionmentioning
confidence: 58%
“…25,26 Taken together, a birth cohort effect should be taken into account in the age-dependent rise in HTLV-I prevalence. 27 This effect observed in this study for HTLV-I suggests that improved screening strategies might be applied to 35 and above years old in Mashhad. On the other hand, a population-based study in French Guiana reported an HTLV-I infection in subjects with all age groups suggesting that other factors might be involved in virus transmission.…”
Section: Discussionmentioning
confidence: 58%
“…The sequences in the LTR phylogenetic tree are reported elsewhere (12,13,23,24,46,49,50). donated blood, the prevalences being 0.33% in Guadeloupe and 0.4% in Martinique in 1999 (5,37).…”
Section: Discussionmentioning
confidence: 96%
“…in blood donors has been found in Jamaica (2.1%) (12). Such comparisons must be made cautiously because screening tests, specificity in marker levels, and medical selection of blood donors can vary from one study to another, but we have attempted to accomplish standard screening tests.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is also well documented in previous studies, which could be explained by a cohort effect (14) and by cumulative effect of infections occurring over the lifetime of individuals, such as by heterosexual transmission. The age-dependent rise in HTLV-1 prevalence could also be explained by a birth cohort effect (12).…”
Section: Discussionmentioning
confidence: 99%